Learning Methodology of Tahfiz Al-Qur'an in Islamic Elementary School - Rizki, Badri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study is to identify the Tahfiz Al-Qur'an learning methodology used by students at Rabbani Islamic Elementary School and Al-Khansa Islamic Elementary School, as well as the current challenges experienced by teachers in teaching Tahfiz Al-Qur'an. This study used a multi-site, qualitative methodology. Tahfiz Al-Qur'an activities at Rabbani Islamic Elementary School and Al-Khansa Islamic Elementary School provided the research data. The information gathered from pupils, teachers, and other school stakeholders. Interviews, observation, and documentation were used to collect the data. Data reduction, data presentation, data verification, and conclusion were employed in the data analysis. The result of this study was the learning this Al-Qur'an applied the Muraja'ah and Tikrar systems. Muraja'ah is a way of repeating memorization and adding new ones. Meanwhile, the Takrir system is used to add new memorization. The Takrir method allows the information that enters short-term memory to go directly to long-term memory by repeating memorization. This can be seen in the teaching and learning activities during this Al-Qur'an learning. It can be seen that, with the pledge method, the teacher reads, and the students follow the teacher's reading of the Qur'an. Meanwhile, with the Muraja'ah method, teachers and students read memorized verses of the Al-Qur'an together. Obstacles faced by Rabbani Islamic Elementary School and Al-Khansa Islamic Elementary School in producing Al-Quran memorizers are that students feel bored with the system that is applied, and the system and method are so monotonous without any variation in learning. Thus the need for several efforts to overcome children's difficulties in memorizing the Al-Qur'an, such as holding motivational seminars on memorizing the Al-Qur'an, varied teaching methods, and grouping students. Thus, the target memorization was achieved quickly.